Shear Bearing Capacity of Framework Joints of Steel-Reinforced Concrete-Filled Circular Steel Tube. (16th January 2020) - Lin, Yongjun; Liu, Kaiqi; Xiao, Tianxu; Zhou, Chang
Abstract : In this paper, in order to investigate the shear mechanism and shear capacity of framework joints of steel-reinforced concrete-filled circular steel tube (SRCFCST), a numerical finite element model reflecting the mechanical behavior of framework joints of SRCFCST column-reinforced concrete beam is established through simulating concrete by the damage plastic constitutive model and simulating steel by the ideal elastic-plastic material, and its effectiveness is verified by experimental data. On account of uniform distribution of circular steel reinforced around the section and without definite flange and web, the shear mechanism of the framework joints of SRCFCST is analyzed on the basis of equivalent circular steel tube (CST) to the rectangular steel tube. The method for calculating the superposed shear bearing capacities of the joint core area is proposed, which is composed of four parts, i.e., concrete inside tube, concrete outside tube, hooping and steel-reinforced web; and the corresponding formulas for calculating shear bearing capacity are established. The comparative analysis of joints' shear bearing capacity indicates that the results of numerical simulation and shear bearing capacity formulas coincide well with the experimental values, which can provide reference for the nonlinear analysis and engineering design of similar joints.